Effect of agrochemical use on rice farmers health in Niger and Ogun States, Nigeria - Oseghale, Agatha Itohan (Journal of Tropical Agriculture, 2022)
The use of agrochemical has led to increase in crop yield. However, its utilization has been associated with some negative health and socio- economic effects. Therefore, this study assessed the effect of agrochemical use on rice farmers’ health. A structured questionnaire was used to obtain cross-section data from 304 rice farmers in Niger and Ogun States, Nigeria, through a multi-stage sampling procedure. Data were analyzed through the use of descriptive statistics and Multivariate Probit (MVP) regression. Results showed that rice farming was carried out by males (91.2%) who had at least primary education (63.8%) with an average age of 44 years. Fertilizer (32.9%) and herbicide (28.4%) were the most common agrochemical utilized while hat (47.5%), nose guard (37.0%) and boots (35.3%) were the protective kits commonly used during agrochemical application. Rice farmers in the study area used banned chemicals of paraquat, 2-4D and propanil without optimally utilizing them. Nearly 90 per cent of farmers did not follow label guidelines and 58.10 per cent of farmers suffered from cough due to agrochemical use. The MVP regression revealed that rice farmers who applied herbicides (â = 0.501, p<0.05) and those who revisited their farms within 24h of spray (â = -0.542, p<0.01) had a higher probability of experiencing skin diseases. The study recommends that assessment, monitoring and environmental implications of agrochemical should be reinforced by the relevant agency before allowing its use. The engaging of children for agrochemical application should be discouraged.